Parasite-induced ER stress response in hepatocytes facilitates Plasmodium liver stage infection - Inácio, Patricia; Mair, Gunnar R. (EMBO reports, 2015)
Abstract Upon infection of a mammalian host, Plasmodium parasites first replicate inside hepatocytes, generating thousands of new parasites. Although Plasmodium intra-hepatic development represents a substantial metabolic challenge to the host hepatocyte, how infected cells respond to and integrate this stress remains poorly understood. Here, we present proteomic and transcriptomic analyses, revealing that the endoplasmic reticulum (ER)-resident unfolded protein response (UPR) is activated in host hepatocytes upon Plasmodium berghei infection. The expression of XBP1s?the active form of the UPR mediator XBP1?and the liver-specific UPR mediator CREBH is induced by P. berghei infection in vivo. Furthermore, this UPR induction increases parasite liver burden. Altogether, our data suggest that ER stress is a central feature of P. berghei intra-hepatic development, contributing to the success of infection.
Gesehen am 03.06.2020